Is Customers’ Financial Reporting Quality Associated with Suppliers’ Decision to Contract? - Naidu, Dharmendra; Ranjeeni, Kumari (The Accounting Review, 2024)
ABSTRACT Using a unique hand-collected dataset of purchase obligations, we find that customers’ financial reporting quality is positively associated with future supply contracts, indicating that suppliers are more willing to contract with customers who provide them with better information. Further, the association between customers’ financial reporting quality and future supply contracts is stronger for customers with strong bargaining power, which is consistent with suppliers relying more on financial reports when they have less access to customers’ private information. Collectively, our results suggest that customers’ financial reporting quality plays an important role in influencing suppliers’ decisions to contract with customers for the future supply of goods and services. Data Availability: Data for dependent variable are manually collected and data for all other variables are available from public sources cited in the text. JEL Classifications: D80; M41.